Bayesian One- Way Repeated Measurements Model Based on Bayes Quadratic Unbiased Estimator (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
In this paper, bayesian approach based on Bayes quadratic unbiased estimator is employed to the linear one- way repeated measurements model which has only one within units factor and one between units factor incorporating univariate random effects as well as the experimental error term. The prior information obtained by using variance analysis technique to represent prior estimates of the parameters of the model. Then, the prior distribution is considered as a uniform distribution.